2018
DOI: 10.4103/jnrp.jnrp_97_18
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein-Associated Phospholipase A2 is Linked with Poor Cardio-Metabolic Profile in Patients with Ischemic Stroke: A Study of Effects of Statins

Abstract: Objectives:The objective of the study is to investigate the effects of statins on the lipoprotein-associated phospholipase A2 (Lp-PLA2) mass in patients with ischemic stroke.Materials and Methods:A total number of 59 patient ages 43–69 years with cerebral stroke compared to 39 healthy controls that matching the age and body weight. The patients were divided into 32 patients on statins therapy assigned as statins users and 27 patients, not on statins therapy assigned as nonstatins users. Anthropometric and bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…This may be because human Lp-PLA2 is highly glycosylated, which makes it difficult for Lp-PLA2 to bind to HDL-C. And under physiological conditions, Lp-PLA2 is mainly attached to LDL in the circulation. Alkuraishy et al [ 28 ] also reported that in patients with cerebral stroke, Lp-PLA2 mass levels were positively correlated with very low-density lipoprotein. In our previous study, we found that the level of Lp-PLA2 in gestational diabetic rats induced by streptozocin was significantly up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because human Lp-PLA2 is highly glycosylated, which makes it difficult for Lp-PLA2 to bind to HDL-C. And under physiological conditions, Lp-PLA2 is mainly attached to LDL in the circulation. Alkuraishy et al [ 28 ] also reported that in patients with cerebral stroke, Lp-PLA2 mass levels were positively correlated with very low-density lipoprotein. In our previous study, we found that the level of Lp-PLA2 in gestational diabetic rats induced by streptozocin was significantly up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is also known as platelet‐activating factor acetylhydrolase (PAF‐AH) (Dennis, Cao, Hsu, Magrioti, & Kokotos, ; Zhou et al, ). In recent years, its application in atherosclerosis‐associated cardiovascular and cerebrovascular diseases has attracted extensive attention (Alkuraishy, Al‐Gareeb, & Waheed, ; Esenwa & Elkind, ; Gorelick, ). Many early studies have considered that (Elkind, Tai, Coates, Paik, & Sacco, ; Lp‐PLA(2) Studies Collaboration et al, ; Oei et al, ) Lp‐PLA2 can hydrolyze platelet‐activating factors, inhibit thrombosis and alleviate inflammation, and work against atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many early studies have considered that (Elkind, Tai, Coates, Paik, & Sacco, ; Lp‐PLA(2) Studies Collaboration et al, ; Oei et al, ) Lp‐PLA2 can hydrolyze platelet‐activating factors, inhibit thrombosis and alleviate inflammation, and work against atherosclerosis. At present, it has been considered that (Alkuraishy et al, ; Yang et al, ) some kinds of Lp‐PLA2 that can bind with high density lipoprotein (HDL) can hydrolyze oxidized phospholipids in blood, reduce the accumulation of inflammatory mediators in phagocytes, and inhibit foam cell formation, thereby exerting anti‐inflammatory and anti‐atherosclerotic effects. In the process of the hydrolysis of oxidized low‐density lipoprotein (ox‐LDL), sLp‐PLA2 produces oxidized free fatty acids (ox‐FFA) and lysolecithin (lyso‐PC) (Bonnefont‐Rousselot, ; Ulrich et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, results of the present study revealed that rosuvastatin improved insulin sensitivity in a dose-dependent manner as 40 mg/kg rosuvastatin led to the improvement of IR with reduction in the insulin release due to the inhibition of gluconeogenesis through the modulation of peroxisome proliferative-activated receptor-γ coactivator-1 (PGC-1α) pathway. [2728]…”
Section: Discussionmentioning
confidence: 99%